Analisis Yuridis Pemutusan Bantuan Program Keluarga Harapan terhadap Keluarga Penerima Manfaat dalam Perspektif Siyasah Dusturiyyah (Studi di Desa Pematang Sei Baru) - Aisyah, Siti; Tanjung, Dhiauddin (Journal of Legal Sustainability, 2026)
This study aims to analyze the mechanism for terminating PKH assistance for Beneficiary Families (KPM) in Pematang Sei Baru Village, identify the factors leading to such termination, and evaluate its compliance with applicable legal regulations and the perspective of siyasah dusturiyyah (Islamic constitutional governance). The study employs a socio-legal (juridical-empirical) method with a qualitative approach, utilizing observation, interviews, and documentation techniques. The results indicate that out of 315 active KPMs, 28 experienced assistance termination. The primary causes for termination were invalid administrative data and changes in welfare decile rankings within the Integrated Social Welfare Data (DTKS) system. From a legal standpoint, the termination process adhered to Minister of Social Affairs Regulation Number 1 of 2018; however, substantively, its implementation did not fully satisfy the principle of justice, as there remained KPMs who were economically eligible to receive the assistance. From the perspective of siyasah dusturiyyah, the policy did not fully reflect the principles of justice, trustworthiness (amanah), and public interest (maslahah). This study contributes by offering recommendations to improve the verification and data-updating mechanisms for PKH—addressing both government systems and active community participation—to ensure that social assistance policy implementation becomes more accurately targeted, transparent, and equitable.